LOGISTICS MODELING AND FINANCIAL RISK IN GOVERNMENTAL EVENTS: A SYSTEMATIC LITERATURE REVIEW - Lemmertz, Luciano (Journal of Interdisciplinary Debates, 2025)
Large-scale governmental events, such as municipalist conferences and public manager summits, pose highly complex logistical and financial challenges. The effective management of these events requires a sophisticated integration of precise demand modeling, operational planning, and the mitigation of inherent financial risks. This paper presents a systematic literature review from the last five years on the intersection of logistics modeling and financial risk management in the context of governmental events. The methodology involved a structured search of academic databases, analyzing demand forecasting models, capacity management strategies like overbooking, and risk management frameworks in public procurement. The results indicate that while the literature on event logistics and risk management is robust in sectors such as hospitality and healthcare, there is a significant gap in the direct application of these models to the specific domain of governmental events. Revenue management practices, such as overbooking based on machine learning-powered no-show predictions, show great potential for optimizing occupancy and mitigating financial losses. Similarly, principles from humanitarian and disaster logistics offer valuable frameworks for managing operations in high-uncertainty, large-scale scenarios. The article concludes by synthesizing the main applicable models and proposing a future research agenda focused on developing integrated and empirically validated frameworks for governmental event management, aligning academic theory with the practical challenges faced by organizers.